Irritable Bowel Syndrome: What Are the Reasons for Dissatisfaction with the Treatment of Patients and Doctors? (Based on the Experience of Medical Institutions of the Northwestern Federal District of Russia) - A. Yu. Baranovsky; T. V. Reshetova; I. S. Sakeyan (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Аim: analyze the results of an anonymous survey of patients with irritable bowel syndrome (IBS) to assess the degree of their satisfaction with the results of the therapy and, on this basis, determine the most optimal approaches to treatment. Material and methods. The work was carried out in 8 subjects of the North-Western Federal District of Russia. An anonymous survey was conducted in 422 patients with mild to moderate IBS. By assessing the number of people who noted the disappearance or significant decrease in the intensity of the main manifestations of the disease one and three months after treatment, the effectiveness of complex therapy was studied. Among the patients included in the study, people with a mixed variant of IBS with a predominance of pain syndrome (n = 206) self-assessed abdominal pain using a visual pain intensity scale. The rest (n = 216) completed a self-assessment of their condition using the frequency of bowel movements and the Bristol Stool Form Scale. In each of these groups, three subgroups were formed: Subgroup 1 — treatment of patients with gastroenterological drugs; Subgroup 2 — treatment with combined pharmacotherapy (with the appointment of psychotropic drugs); Subgroup 3 — treatment with a combination of gastroenterological and psychotropic drugs and the use of non-medicinal methods of psychotherapy.Results. The maximum difference in the subjective satisfaction of patients with their treatment was noted three months after the completion of the course of treatment in Subgroup 3 (79 % — mild IBS, 71 % — moderate IBS). Patients of Subgroup 2 after three months positively assessed the results of their treatment in 34 and 27 % of cases, respectively. In patients of Subgroup 1, the considered indicators were even less significant — 28 % (mild IBS) and 22 % (moderate IBS).Conclusion. The treatment complex for IBS patients can be considered optimal if, in addition to symptomatic medications, appropriate psychotropic medications are necessarily included in it basing on diagnostic assessment of the psychoemotional status of a particular patient, as well as the appointment of individually selected non-medicinal methods of psychological correction in accordance with psychosomatic symptoms. Full-time cycles on psychodiagnostics and psychotherapy should be included in the educational programs of advanced training of doctors working with IBS patients.